Multimodal imaging evaluation of combined hamartoma of the retina and retinal pigment epithelium. Issue 3 (May 2020) - Scupola, Andrea; Grimaldi, Gabriela; Sammarco, Maria G; Sasso, Paola; Marullo, Michele; Blasi, Maria A
Purpose: Combined hamartoma of the retina and retinal pigment epithelium is a rare benign tumor characterized by a variable combination of glial, vascular, and pigmented components. The purpose of our study was to analyze the features of combined hamartoma of the retina and retinal pigment epithelium on optical coherence tomography angiography. Methods: Small case series of two cases of combined hamartoma of the retina and retinal pigment epithelium with macular and optic nerve involvement, evaluated with multimodal imaging including optical coherence tomography, fluorescein angiography, and optical coherence tomography angiography. Results: On optical coherence tomography, combined hamartoma of the retina and retinal pigment epithelium is characterized by disruption of the inner neurosensory retina and a variable degree of involvement of the external retina. Optical coherence tomography angiography showed diffuse alterations of the retinal vessels of the superficial and deeper layers, extended to the peripapillary area. Vessel abnormalities included increased tortuosity and caliber of vessels, vascular traction, and vessel stretching within the lesion. Conclusion: Optical coherence tomography angiography allows in-depth multilayer analysis of tumor vascular network, highlighting the fine abnormalities of retinal vasculature characteristic of combined hamartoma of the retina and retinal pigment epithelium.